Combination adjuvant chemotherapy with targeted drugs for treatment of colorectal cancer: A network meta‐analysis. Issue 2 (24th November 2017) - Wang, Jinghui; Luo, Li; Wang, Dingxue; Guo, Bin; Li, Jun; Yang, Zhu; Tang, Dongxin
Abstract: Colorectal cancer (CRC) is one of the most fatal diseases in the world. The efficacy of present chemotherapy treatments are limited and the addition of targeted drugs have been put into practice. However, the preferred treatments among adjuvant chemotherapies still remain controversial and uncertain. To evaluate the efficacy of different adjuvant chemotherapies combined with or without targeted drugs to determine the optimal treatment for patients with CRC in clinical practice. PubMed and Embase were searched for eligible articles and only randomized controlled trials (RCTs) were included. R (Version 3.2.5) software was utilized to conduct the Bayesian network meta‐analysis (NMA). Outcomes including overall survival (OS) and progression‐free survival (PFS) were displayed using hazard ratios. And the rank probabilities of each treatment were evaluated using the surface under cumulative ranking curve. A total of 75 RCTs published after 1997 were included in the data analysis. Overall, FOLFIRI+ cetuximab was found to be the most effective treatment in terms of long‐term survival and FOLFOX was the most effective pure chemotherapy treatment. The addition of targeted drugs will greatly improve the efficacy of chemotherapy. Targeted drug cetuximab combined with the chemotherapy regiment FOLFIRI is the preferable treatment for patients with CRC in clinical practice. Abstract : The addition of targeted drugs will greatly improve the efficacy of chemotherapy generally. Targeted drug C plus chemotherapy regiment FOLFIRI is the preferable treatment for patients with CRC in clinical practice.